2015
DOI: 10.1262/jrd.2015-056
|View full text |Cite
|
Sign up to set email alerts
|

The luteotrophic function of galectin-1 by binding to the glycans on vascular endothelial growth factor receptor-2 in bovine luteal cells

Abstract: The corpus luteum (CL) is a temporary endocrine gland producing a large amount of progesterone, which is essential for the establishment and maintenance of pregnancy. Galectin-1 is a β-galactose-binding protein that can modify functions of membrane glycoproteins and is expressed in the CL of mice and women. However, the physiological role of galectin-1 in the CL is unclear. In the present study, we investigated the expression and localization of galectin-1 in the bovine CL and the effect of galectin-1 on cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…The O‐glycan‐mediated binding of galectin‐1 to NRP‐1 further activates another angiogenic protein, vascular endothelial growth factor receptor 2 (VEGFR2). In fact, galectin‐1 can directly bind to the LacNAc residues in VEGFR2 21 . As a result, the downstream proteins of mitogen‐activated protein kinases (MAPK) signaling pathway get activated eventually leading to the activation of angiogenic processes such as proliferation, migration, and tube formation in endothelial cells 14,21–26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The O‐glycan‐mediated binding of galectin‐1 to NRP‐1 further activates another angiogenic protein, vascular endothelial growth factor receptor 2 (VEGFR2). In fact, galectin‐1 can directly bind to the LacNAc residues in VEGFR2 21 . As a result, the downstream proteins of mitogen‐activated protein kinases (MAPK) signaling pathway get activated eventually leading to the activation of angiogenic processes such as proliferation, migration, and tube formation in endothelial cells 14,21–26 .…”
Section: Introductionmentioning
confidence: 99%
“…21 As a result, the downstream proteins of mitogen-activated protein kinases (MAPK) signaling pathway get activated eventually leading to the activation of angiogenic processes such as proliferation, migration, and tube formation in endothelial cells. 14,[21][22][23][24][25][26] An earlier report demonstrated that the inhibition of galectin-1-stimulated angiogenesis with anginex, a designed anti-angiogenic peptide, leads to impaired angiogenesis and poor placentation and provokes pre-eclampsialike symptoms with intrauterine fetal growth restriction in mice. 25 Pre-eclampsia is a vascular disease of the placenta that arises during pregnancy in association with hypertension and proteinuria.…”
Section: Introductionmentioning
confidence: 99%